Social Protection of Women in Uzbekistan - As an Important Link of Reforms - Ergasheva Gulchehra Kuldashevna; Ruzieva Dilshoda Mavlonovna (International Journal on Integrated Education, 2022)
This article focuses on the protection of women's rights and interests in Navoi region, ensuring women's participation in all legal, economic, political, spiritual and educational spheres of social life, improving the socio-spiritual environment in neighborhoods and families, targeted support for disadvantaged women, the article states that it is an important task to study their living conditions and provide practical assistance.